Thermoresponsive chitosan–agarose hydrogel for skin regeneration - Miguel, Sónia Alexandra Pereira (2018)
Healing enhancement and pain control are critical issues on wound management. So far, different wound dressings have been developed. Among them, hydrogels are the most applied. Herein, a thermoresponsive hydrogel was produced using chitosan (deacetylation degree 95%) and agarose. Hydrogel bactericidal activity, biocompatibility, morphology, porosity and wettability were characterized by confocal microscopy, MTS assay and SEM. The performance of the hydrogel in the wound healing process was evaluated through in vivo assays, during 21 days. The attained results revealed that hydrogel has a pore size (90–400 μm) compatible with cellular internalization and proliferation. A bactericidal activity was observed for hydrogels containing more than 188 μg/mL of chitosan. The improved healing and the lack of a reactive or a granulomatous inflammatory reaction in skin lesions treated with hydrogel demonstrate its suitability to be used in a near future as a wound dressing.